2006
DOI: 10.1111/j.1469-0691.2005.01331.x
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of vancomycin-resistant Enterococcus spp. in an Italian general intensive care unit

Abstract: Following the identification of two clinical isolates of vancomycin-resistant enterococci (VRE) from intensive care unit (ICU) patients, a surveillance programme detected that six of eight ICU patients were colonised by VRE. Standard epidemic control measures were instituted in the ICU. During a 16-month period, 13 (2.5%) of 509 ICU patients had VRE-positive swabs upon admission, and 43 (8.7%) of 496 VRE-negative patients were colonised by VRE in the ICU. Patients who acquired VRE in the ICU had a longer ICU s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…And CNS4 (4-1-1-1-1-1-1) which was never reported until now is expected to be new to MLST database. The most common form of STs in Korea is known to be ST78 [20]. But in this CNS3 CNS4 CNS5 CNS6 CNS8 CNS9 CNS10 CNS11 CNS12 CNS13 CNS14 CNS15 CNS16 CNS17 CNS18 CNS19 CNS20 CNS22 CNS23 CNS24 CNS25 CNS27 CBS2 CBS3 CBS6 CBS7 CBS8 CBS9 CBS11 CBS12 CBS14 EJS1 EJS2 EJS3 EJS4 EJS5 EJS7 78 New 192 78 192 78 78 192 192 78 192 192 192 78 192 192 78 192 192 192 192 17 17 78 78 192 192 414 192 192 78 192 192 78 78 192 …”
Section: Discussionmentioning
confidence: 99%
“…And CNS4 (4-1-1-1-1-1-1) which was never reported until now is expected to be new to MLST database. The most common form of STs in Korea is known to be ST78 [20]. But in this CNS3 CNS4 CNS5 CNS6 CNS8 CNS9 CNS10 CNS11 CNS12 CNS13 CNS14 CNS15 CNS16 CNS17 CNS18 CNS19 CNS20 CNS22 CNS23 CNS24 CNS25 CNS27 CBS2 CBS3 CBS6 CBS7 CBS8 CBS9 CBS11 CBS12 CBS14 EJS1 EJS2 EJS3 EJS4 EJS5 EJS7 78 New 192 78 192 78 78 192 192 78 192 192 192 78 192 192 78 192 192 192 192 17 17 78 78 192 192 414 192 192 78 192 192 78 78 192 …”
Section: Discussionmentioning
confidence: 99%
“…MLST of representative MT-159 isolates (also from the three hospitals not included in the study) revealed ST-78. Nosocomial outbreaks of ST-78 have been described in Korea and Europe, including Germany and Italy (1,14,16,24).…”
Section: Vol 46 2008 Emergence Of Cc17 E Faecium 217mentioning
confidence: 99%
“…Most cases are those with mere colonization of the gastrointestinal tract. However, VRE strains may act as etiological agents of serious urinary and respiratory infections and generalized sepses 11 .…”
Section: Discussionmentioning
confidence: 99%